2020
DOI: 10.1111/cid.12964
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary sinus augmentation with three different biomaterials: Histological, histomorphometric, clinical, and patient‐reported outcomes from a randomized controlled trial

Abstract: Background Lateral maxillary sinus augmentation (MSA) is a predictable bone regeneration technique in case of atrophy of the posterior‐upper maxilla. Aimed at obtaining quantity and quality of bone suitable for receiving osseointegrated implants, its success is largely due to the skill of the surgeon, but also to the characteristics of the biomaterial used. Methods Twenty‐four patients needing MSA were included in the study. The patients were randomly allocated to three different groups: anorganic bovine bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Scientific evidence showed that MSFA predictably leads to high implant survival rates, limited peri-implant marginal bone loss, and resulted in few overall surgical and prosthetic complications in maxillary patients [ 3 , 4 , 5 , 6 , 7 , 8 ]. The lateral osteotomy technique to approach the MFSA for increasing bone volume in the posterior maxilla is a well-established and documented surgical procedure allowing for implant placement [ 3 , 13 , 14 , 31 ]. Irrespective of the grafting materials applied (i.e., autogenous bone, allografts, xenografts, alloplastic), MFSA is accompanied by increased implant stabilization and new bone formation [ 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scientific evidence showed that MSFA predictably leads to high implant survival rates, limited peri-implant marginal bone loss, and resulted in few overall surgical and prosthetic complications in maxillary patients [ 3 , 4 , 5 , 6 , 7 , 8 ]. The lateral osteotomy technique to approach the MFSA for increasing bone volume in the posterior maxilla is a well-established and documented surgical procedure allowing for implant placement [ 3 , 13 , 14 , 31 ]. Irrespective of the grafting materials applied (i.e., autogenous bone, allografts, xenografts, alloplastic), MFSA is accompanied by increased implant stabilization and new bone formation [ 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lateral osteotomy technique to approach the MFSA for increasing bone volume in the posterior maxilla is a well-established and documented surgical procedure allowing for implant placement [ 3 , 13 , 14 , 31 ]. Irrespective of the grafting materials applied (i.e., autogenous bone, allografts, xenografts, alloplastic), MFSA is accompanied by increased implant stabilization and new bone formation [ 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, the superior osteogenic and osteoinductive capacities of autogenous bone could be beneficial in short-term healing. Clinically, no significant differences in new bone formation were observed in using allogeneic, xenogeneic, or synthetic bone substitutes with or without autogenous bone [67,96,100]. Possible clinical considerations of usage of bone substitutes over autografts include reducing invasiveness of surgery and surgical time [67].…”
Section: Maxillary Sinus Augmentationmentioning
confidence: 99%
“…Conflicting findings exist in regard to comparing healing periods between these two groups and if the success of the maxillary sinus augmentation is dependent on the graft materials used [96]. Overall, regardless of which biomaterials are used, maxillary sinus augmentation is safe and well-tolerated by patients [100].…”
Section: Maxillary Sinus Augmentationmentioning
confidence: 99%